Diagnostyka i postępowanie w grzybiczych zakażeniach rogówki - Rymgayłło-Jankowska, Beata; Rakowska, Ewa; Haszcz, Dariusz; Kudasiewicz-Kardaszewska, Agnieszka; Suchodoła-Ratajewicz, Ewa; Bielińska, Agnieszka; Zagórski, Zbigniew (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
Fungal keratitis, an important cause of corneal infectious disease, is one of the most challenging types of microbial keratitis to diagnose, isolate the etiologic fungal organism and treat successfully. Aspergillus spp. are most commonly responsible for fungal keratitis worldwide. Most cases occur in hot, humid climates. Fungi invade the ocular surface only when it is compromised and gain access into the corneal stroma through a defect in the epithelial barrier. Pathogens multiply then, and cause inflammatory reaction together with tissue necrosis. Symptoms of fungal keratitis typically are not as acute as those of other forms of microbial keratitis. On examination, both signs seen in other forms of microbial keratitis and specific features of fungal keratitis are observed. In all cases with suspected fungal keratitis, corneal smears and cultures should be performed as soon as possible. Antifungal therapy should be restricted to those cases with fungus-positive laboratory results. The use of topical corticosteroids in the treatment of fungal keratitis is contraindicated. In about one-third of patients pharmacological therapy is not successful. In those cases, surgical intervention is essential. The main goal of surgical intervention is to control infection and maintain the integrity of the globe. The most commonly performed surgery in fungal keratitis is therapeutic penetrating keratoplasty. The use of topical corticosteroids is contraindicated in early postoperative period.